Innovation barriers and risks for food processing SMEs in Malaysia: a logistic regression analysis - Nor Ghani Mohd Nor,; Abu Bashar Bhuiyan,; Jamaliah Said,; Syed Shah Alam, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
The food industry is facing a period of rapid change driven by globalization, trade liberalization, development of genetic, processing and information technology, intellectual property rights, changes in family structure and health and food safety concerns. Given that the food processing SMEs account for a large part of mainstream businesses in Malaysia, this study sought to examine the impact of barriers and risks on the innovation of new product, process and services of food processing SMEs in Malaysia. To achieve this objectives, the study analysed primary data gathered from 247 executives of food processing SMEs in Malaysia with statistical and econometric techniques. The multiple logistic regression models were employed to estimate how innovations were being affected by the existing barriers. The study revealed that the Malaysian SMEs were suffering from financial sourcing problems and beset with the barriers of human capital, business competitiveness, infrastructure, and government policy. Further multiple logistic regression model’s outputs showed significant impacts on innovations from financial barriers, especially in regard to financial assistance from the government or financial institutions, namely, high interest rates or profit charged, complicated loan application process and unable to enjoy promotional financial packages by financial institutions for food processing SMEs in Malaysia. The study recommended that the Malaysian SMEs’ challenges be considered seriously and that the industry be provided with sufficient financial assistance in developing new products, new market and new sources of supply so that they can be truly sustainable and globally competitive.